AIR GANDARUSA (Justicia gendarussa Burm. f.) DAN GAMBARAN GEN HYALURONIDASE LEWAT ANALISIS PCR - Sri Lestari Utami; Didik P. Restanto; Bambang Prajogo EW (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Gandarusa (J. gendarussa Burm. f.) is an etnomedicine which is used as a male contraceptive alternative, known to inhibit the enzymefunction of spermatozoa hyaluronidase during fertilization. One of the ideal contraceptive conditions is the safetyness (among others nonmutagenic), requiring a long research during the verification process. The early research is the gene expression of hyaluronidase mice(M.musculus L.) testis given water fraction of the gandarusa with PCR analysis. The total RNA was isolated from the normal mice testis(as the negative control or no treatment group) and the mice testis from the treatment groups. The treatment groups consisted of group Iand II treated with water fraction of the gandarusa 15 mg/20 gr BW and 7.5 mg/20 gr BW, subsequently, the positive control group wasalso given hesperidins 1 mg/20 gr BW once a day per oral during the 1.5 times of spermatogenesis cycle (for 55 days). The results of thestudy showed that (1) the cDNA fragment confirmed as the gene of hyaluronidase mice testis (with 710 bp length of nucleotide) passedthrough RT-PCR at the total RNA negative control group, sequenced, isolated and alignment in the NCBI gene bank. (2) the same cDNAfragment gene of hyaluronidase mice testis (from the negative control group) did not transcript in the treatment I and positive controlgroups (where there is no band), but this gene will be transcripted in the treatment II group (where the band is emerged).